2003
DOI: 10.1590/s0100-204x2003001100004
|View full text |Cite
|
Sign up to set email alerts
|

Toxicidade de antibióticos no cultivo in vitro da batata em meios semi-sólido e líquido

Abstract: Resumo -O objetivo deste trabalho foi avaliar os efeitos fitotóxicos de antibióticos no crescimento e na taxa de multiplicação in vitro da batata. Brotações da cultivar Baronesa foram cultivadas em meio de multiplicação de consistência semi-sólida e líquida. O meio de multiplicação foi formado pelos sais e vitaminas de MS ao qual adicionou-se um dos seguintes antibióticos: ampicilina, cloranfenicol, estreptomicina e tetraciclina, previamente selecionados em razão da ação bactericida sobre contaminantes da cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
2
4
0
4
Order By: Relevance
“…Entre os demais tratamentos: T 2 (cloranfenicol 30 mg L -1 ); T 3 (ampicilina sódica 250 mg L -1 ); T 4 (ácido nalidíxico 500 mg L -1 ); T 6 (tetraciclina 500 mg L -1 ), e T 7 (norfloxacina 400 mg L -1 ) também não houve diferença significativa (Tabela 1). Pereira et al (2003), estudando bactérias endofíticas contaminantes da cultura in vitro da batata (Solanun tuberosum), observaram que entre doze antibióticos testados, seis apresentaram algum tipo de controle e, destes, os melhores resultados foram proporcionados pela ampicilina, cloranfenicol, estreptomicina e tetraciclina.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Entre os demais tratamentos: T 2 (cloranfenicol 30 mg L -1 ); T 3 (ampicilina sódica 250 mg L -1 ); T 4 (ácido nalidíxico 500 mg L -1 ); T 6 (tetraciclina 500 mg L -1 ), e T 7 (norfloxacina 400 mg L -1 ) também não houve diferença significativa (Tabela 1). Pereira et al (2003), estudando bactérias endofíticas contaminantes da cultura in vitro da batata (Solanun tuberosum), observaram que entre doze antibióticos testados, seis apresentaram algum tipo de controle e, destes, os melhores resultados foram proporcionados pela ampicilina, cloranfenicol, estreptomicina e tetraciclina.…”
Section: Resultsunclassified
“…Diversas pesquisas têm sido realizadas para a prevenção ou eliminação dos contaminantes do cultivo in vitro de plantas, desde o desenvolvimento de protocolos de assepsia, cuidados com as plantasmatrizes, até o uso de produtos antimicrobianos, adicionados ao meio de cultura (PEREIRA et al, 2009). Biasi (1995) testou a adição, ao meio de cultura, de diferentes doses dos antibióticos ácido nalíxico, cloranfenicol e estreptomicina, para o controle in vitro de bactérias, em segmentos nodais e discos foliares de abacateiro.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Other studies have also demonstrated the toxicity symptoms caused by antibiotics in explants from different plant species. In potato in vitro culture, Pereira and Fortes (2003) reported severe phytotoxic effects on the growth and explant multiplication rate as a function of increasing concentrations (0,32,64,128,256,512, and 1024 mg/L) of chloramphenicol, streptomycin, and tetracycline in the culture medium. In the study of Chalak et al (2005), no plant was regenerated from 1-cm microcuttings subjected to treatments with 50, 100, and 150 µg/mL oxytetracycline for phytoplasma cleaning (Candidatus Phytoplasma phoenicium) in almond tree varieties.…”
Section: Antibiotic Treatmentsmentioning
confidence: 99%
“…In potatoes, for example, Pereira and Fortes (2003) reported that ampicillin was the only antibiotic that did not affect the survival and development of shoots for the multiplication, even at the highest concentration (1.024 g/L), and after a 21-day culture, there was about 100% survival explants. Pereira and Fortes (2003) emphasized that the l antibiotics, chloramphenicol, streptomycin, and tetracycline, negatively affected the in vitro development of potato, causing a significant decrease in shoot height and multiplication rate along with the increase of their concentrations in the culture medium. Moreover, Ćurković-Perica and Ježić (2010) reported that in Catharanthus roseus (L.) G. Don, none of the quercetin concentrations (10, 100, or 1 mM) showed efficient cleaning of plants infected with phytoplasma.…”
Section: Antibiotic Treatmentsmentioning
confidence: 99%